Surface modification of polyhedral nanocrystalline MgO with imidazolium carboxylates for dehydration reactions: a new approach. Issue 86 (31st August 2016) - Shaikh, Melad; Sahu, Mahendra; Khilari, Santimoy; Kumar, Atyam Kiran; Maji, Pathik; Ranganath, Kalluri V. S.
Abstract : The surface of nanocrystalline MgO was modified with achiral and chiral imidazolium carboxylates which generate MgO–[NHC] complexes. Thus as synthesized complexes were utilized in the dehydration of glucose and also in selective dehydration of (±) nitro alcohol. Abstract : The surface modification of nanomaterials with organic molecules and the utilization of modified materials in various applications is equally important. Here we demonstrate, the surface modification of polyhedral nano MgO with imidazolium carboxylate, which generates the NHC stabilized material MgO–[NHC]. The resultant material was successfully utilized in the catalytic dehydration of glucose under heterogeneous conditions. Furthermore, it was used in the dehydration of nitro alcohol to olefins in high yields. In addition, the surface modified catalyst was characterized by using various techniques like XRD, FE-SEM, TEM, FT-IR, XPS and AES analysis.